Src Inhibits the Hippo Tumor Suppressor Pathway through Tyrosine Phosphorylation of Lats1 - Si, Yuan; Ji, Xinyan; Cao, Xiaolei; Dai, Xiaoming; Xu, Lingyi; Zhao, Hongxia; Guo, Xiaocan; Yan, Huan; Zhang, Haitao; Zhu, Chu; Zhou, Qi; Tang, Mei; et al. (Cancer research (Chicago, Ill.), 2017)
The Hippo pathway regulates cell proliferation, apoptosis, and stem cell self-renewal, and its inactivation in animal models causes organ enlargement followed by tumorigenesis. Hippo pathway deregulation occurs in many human cancers, but the underlying mechanisms are not fully understood. Here, we report tyrosine phosphorylation of the Hippo pathway tumor suppressor LATS1 as a mechanism underlying its regulation by cell adhesion. A tyrosine kinase library screen identified Src as the kinase to directly phosphorylate LATS1 on multiple residues, causing attenuated Mob kinase activator binding and structural alteration of the substrate-binding pocket in the kinase domain. Cell matrix adhesion activated the Hippo pathway effector transcription coactivator YAP partially through Src-mediated phosphorylation and inhibition of LATS1. Aberrant Src activation abolished the tumor suppressor activity of LATS1 and induced tumorigenesis in a YAP-dependent manner. Protein levels of Src in human breast cancer tissues correlated with accumulation of active YAP dephosphorylated on the LATS1 target site. These findings reveal tyrosine phosphorylation of LATS1 by Src as a novel mechanism of Hippo pathway regulation by cell adhesion and suggest Src activation as an underlying reason for YAP deregulation in tumorigenesis. Cancer Res; 77(18); 4868–80. ©2017 AACR.